USING SYNTACTIC UNITS IN THE LANGUAGE OF FILM ACTORS - Mustafayev Fizuli Najmaddin (International Journal of Innovative Technologies in Social Science, 2020)
The article is devoted to the use of syntactic units in the language of film actors. The article draws attention to various ideas and considerations regarding the use of syntactic units in all areas of the cinematic language. The reader is presented about themes, genres, style problems in Azerbaijani cinema, screen artists, large-format publishing, a variety of styles in the director’s work, various problems of cinema and theater poetry, the history of television poetry and style. The differences in some cases between the written language and its oral form, innovation, accent, facial expressions and gestures of the actors by the setting of the pavilion and the fact that the dramatic point of view of the film is conveyed to the reader only by word. Since thought is known in dialogical speech, the narrative of some members of a sentence, complex sentences requiring details are omitted. The film pavilion, structure, actor’s movements, images form the basis of the article. Readers can extract information from all this, especially since directors and actors choose syntactic units that are more suitable for spoken language. The article also provides tips from individual films and presents ideas for any explanation.